Gig Economy Workers: A Systematic Literature Review - Yuliantina, Devi; Yuli Fatmawati; Ainun Jariah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The gig economy has significantly transformed work patterns and labor market dynamics. This study presents a systematic literature review to identify conceptual trends in research on gig economy workers. Employing descriptive analysis, 157 articles from the Scopus database (2017–2023) were analyzed using VOSviewer. The findings reveal three primary concepts: the gig economy, online platforms, and workers. Moreover, the analysis indicates that digital technology positively and negatively impacts gig economy workers, highlighting workers' need to comprehend the digital ecosystem. Policymakers have a pivotal role in ensuring adequate employment protection for these workers. However, this study is limited to data from Scopus and excludes publications from 2024. Future research should include a comparative analysis using the Web of Science (WoS) database and extend the period frame to provide a more comprehensive perspective.